The Use of Social Media as a Learning Media Based on Multiple Representation to Increase Student Learning Motivation: Article Review - Juwita Karina Pratiwi; Hayuni Retno Widarti; Deni Ainur Rokhim (Orbital: The Electronic Journal of Chemistry, 2024)
The use of social media can be used as a learning media as in the learning of chemistry. Utilization of social media as a medium of chemistry learning, is considered capable of increasing student motivation and digital literacy. This study aims to analyze the research trends of social media -based learning media, multiple representations of chemical materials and increase student learning motivation. This research method uses the Systematic Literature Review (SLR). Research data obtained from 20 articles originating from the Eric and Google Scholar database. The SLR method is used to identify, review, evaluate and interpret all studies available in the field of subjects that are of interest to a phenomenon involving certain related research questions. Based on the literature review that has been done it can be concluded that research on social media as a learning medium for hydrolysis of salt -based multiple representation can be done with various considerations of the results of previous research.